BELAJAR DARI MONYET - Rokhmaniyah Rokhmaniyah (Universitas Sarjanawiyata Tamansiswa, 2017)
The Monkey Training Academy indirectly implements progressive paedagogic principles. The Monkey Training Academy also applies the four pillars of education according to UNESCO (learning to know, learning to do, learning to live with others, and learning to be someone). This literature research can inspire educators to be creative. Sources of research data in the form of books